Contribución al conocimiento de la "guinda" (solanum sisymbriifolium lam.) floración-fructificación (1990)
This paper is a contribution to the knowledge of flowering and fruiting of Solanum sisymbriifolium, based on a two-year observation on individual plants growing in two localities (Silvania, 1300 m.a.s.l. and Bogota, 2640 m.a.s.l., Department of Cundinamarca, Colombia). Ripening and senescence processes are succintly described.